2009
DOI: 10.1371/journal.pone.0007257
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genotyping of Campylobacter jejuni Strains from Patients with Guillain-Barré Syndrome in Bangladesh

Abstract: Background Campylobacter jejuni is a common cause of acute gastroenteritis and is associated with post-infectious neuropathies such as the Guillain-Barré syndrome (GBS) and the Miller Fisher syndrome (MFS). We here present comparative genotyping of 49 C. jejuni strains from Bangladesh that were recovered from patients with enteritis or GBS. All strains were serotyped and analyzed by lipo-oligosaccharide (LOS) genotyping, amplified fragment length polymorphism (AFLP) analysis, multilocus sequence typing (MLST),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 41 publications
(55 reference statements)
6
41
0
Order By: Relevance
“…This observation indicates that the development of GBS after Campylobacter infection could vary depending on host factors, even when individuals are infected with seemingly genetically identical strains. Therefore, a correlation between MLST genotypes and the onset of GBS could be difficult to determine, though several studies have found significant associations (38,39). Nonetheless, our result has added further support to the described association between infection with HS:41 and the development of GBS, even from a wild bird source.…”
Section: Discussionsupporting
confidence: 48%
“…This observation indicates that the development of GBS after Campylobacter infection could vary depending on host factors, even when individuals are infected with seemingly genetically identical strains. Therefore, a correlation between MLST genotypes and the onset of GBS could be difficult to determine, though several studies have found significant associations (38,39). Nonetheless, our result has added further support to the described association between infection with HS:41 and the development of GBS, even from a wild bird source.…”
Section: Discussionsupporting
confidence: 48%
“…jejuni strains can be classified by MLST complexes. A number of studies have sought to establish whether there is a link between MLST type and the development of postinfectious complications (Dingle et al, 2001;Nielsen et al, 2010;Islam et al, 2009). It was noted that the ST22 complex is over-represented in isolates from patients who have contracted Guillain-Barré syndrome; no GuillainBarré-related isolates have been shown to carry ST45, despite it being a common sequence type (Dingle et al, 2001;Nielsen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the ST22 complex is over-represented in isolates from patients who have contracted Guillain-Barré syndrome; no GuillainBarré-related isolates have been shown to carry ST45, despite it being a common sequence type (Dingle et al, 2001;Nielsen et al, 2010). No sequence types have been found to be exclusive for clinical outcomes (Islam et al, 2009). This supports the findings of Manning et al (2003), who studied a large number of C. jejuni isolates and found that in terms of MLST types, the populations of veterinary and human isolates overlapped; it was suggested that most veterinary sources should be considered reservoirs of pathogenic campylobacters.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data is available on the association of the LOS classes with ST complexes; however, studies on GBS associated strains have identified ST-22 strains to have LOS class A [8]. In the study of Mortensen et al [24], sialylated LOS class A strains were significantly associated with reactive arthritis as well.…”
Section: Discussionmentioning
confidence: 99%